2015
DOI: 10.1002/2014wr016842
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid‐3D hillslope hydrological model for use in Earth system models

Abstract: Hillslope‐scale rainfall‐runoff processes leading to a fast catchment response are not explicitly included in land surface models (LSMs) for use in earth system models (ESMs) due to computational constraints. This study presents a hybrid‐3D hillslope hydrological model (h3D) that couples a 1‐D vertical soil column model with a lateral pseudo‐2D saturated zone and overland flow model for use in ESMs. By representing vertical and lateral responses separately at different spatial resolutions, h3D is computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 66 publications
(121 reference statements)
0
67
0
Order By: Relevance
“…Recent efforts to explore a new subgrid structure in ALM to represent subgrid topographic variations [ Tesfa and Leung , ] provide a useful modeling framework for developing parameterizations of lateral processes driven by surface topography. For example, the subgrid framework of ALM may be combined with the hybrid 3‐D hillslope hydrological model [ Hazenberg et al , ] where lateral responses are aggregated to the topographic land units of ALM to provide a more computationally efficient method than 3‐D distributed models for simulating both vertical and lateral hydrologic processes in Earth system models. Developing approaches to represent lateral processes, in addition to incorporating plant hydraulics and preferential flow discussed above, are key efforts needed to improve the ability of Earth system models in simulating tropical forest response to drought and the future of the land carbon sink under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts to explore a new subgrid structure in ALM to represent subgrid topographic variations [ Tesfa and Leung , ] provide a useful modeling framework for developing parameterizations of lateral processes driven by surface topography. For example, the subgrid framework of ALM may be combined with the hybrid 3‐D hillslope hydrological model [ Hazenberg et al , ] where lateral responses are aggregated to the topographic land units of ALM to provide a more computationally efficient method than 3‐D distributed models for simulating both vertical and lateral hydrologic processes in Earth system models. Developing approaches to represent lateral processes, in addition to incorporating plant hydraulics and preferential flow discussed above, are key efforts needed to improve the ability of Earth system models in simulating tropical forest response to drought and the future of the land carbon sink under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the push for hillslope-resolving models across large geographical domains, one approach is to use the concept of representative hillslopes (Troch et al, 2003;Hazenberg et al, 2015;Ajami et al, 2016). The representative hillslope has a length dimension much smaller than the length scale of the model element, and the hillslope is discretized into columns along an axis perpendicular to the stream to explicitly resolve lateral flow processes.…”
Section: Modeling Solutionsmentioning
confidence: 99%
“…As noted earlier, recent applications of hydrologic similarity methods have shown that it is possible to reduce run times by 2 to 3 orders of magnitude, without any loss in information content (Newman et al, 2014;Chaney et al, 2016a). Also, hydrologic similarity concepts can be effectively applied using multiscale methods to resolve the dominant spatial gradients that drive flow; for example, using representative hillslopes to explicitly resolve lateral flow processes (Troch et al, 2003;Berne et al, 2005;Hazenberg et al, 2015;Ajami et al, 2016). In exploring these solutions, we recognize that there is not necessarily a tradeoff between physical realism and computational efficiency -the linkage between spatial complexity and process complexity may be rather weak, as models that are run using a large number of spatial elements may still miss dominant processes (e.g., Hartmann et al, 2017).…”
Section: Computing Solutionsmentioning
confidence: 99%
“…An alternative, but related, concept is the representative hillslope (RH; Berne et al, 2005;Hazenberg et al, 2015). The REA-REW approach is conceptually similar to Reynolds averaging, and relies on the fundamental assumption that the physics are known on the smallest scale considered (e.g., Miller and Miller, 1956).…”
Section: Scaling and Similarity Hypothesesmentioning
confidence: 99%